Application of Particle Imaging Method for Measurement of Solid Volume Fraction in Carbon Nanotube Particles Fluidized Bed - Won Kim, Sung; ., . (International Journal of Engineering and Technology, 2018)
Solid volume fraction in the carbon nanotube (CNT) fluidized bed reactors is an important parameter which is responsible of fluidization quality and the design of reactor. The solid volume fraction can be obtained from the pressure drop across the bed with the information of gas and particle densities. However, previous method such as the Hg-porosimetry for the measurement of the particle density did not adequately draw the solid volume fraction of the CNT aggregates with entangled nanotubes network. A new method to measure the apparent particle density of the CNT aggregates was proposed to calculate the solid volume fraction in the CNT fluidized bed. The density of the vertically aligned CNT particle was measured based on the apparent volume by shape analysis using two dimensional imaging. The solid fraction based on imaging method showed a significant value of 0.69 for the fixed bed, which describes well the entangled structure of the CNT aggregates. The distribution of solid volume fraction in the CNT fluidized bed with variation of gas velocity was determined based on the imaging method. The method was verified by applying the obtained values to the Richardson-Zaki equation on the bed expansion in the fluidized bed.Â Â